Let $A=A^+ +A^-$ where $A^+,A^-$ denote the creation and annihilation portion of the field. Then in Eduardo Fradkin, Field Theories of Condensed Matter Physics, equation (5.284), it states that $$ :e^A::e^B: ~=~ e^{[A^+,B^-]}:e^{A+B}:\tag{5.284} $$ where $::$ denotes normal-ordering of $A^+,A^-$. I'm familiar with the regular Baker-Hausdorff formula, but I'm not sure why this identity is true.

EDIT: Here's my attempt. \begin{align} :A^n: &= \text{He}_n(A) \\ :e^A: &= \sum_{n=0}^\infty \frac{1}{n!}\text{He}_n(A) =e^{A-1/2}\\ :e^A::e^B: &= e^{-1} e^A e^B\\ &= e^{-1} e^{A+B} e^{\frac{1}{2} [A,B]} \\ &= :e^{A+B}:e^{-1/2} e^{i \Im[A^+,B^-]} \end{align} where I implicitly assumed that $[A,B]$ is a complex multiple of the identity. However, you can see that my result doesn't quite match the equation.


Ref. 1 contains several$^1$ typos, e.g. the aforementioned eq. (5.284) if we use$^1$ the definition above eq. (5.262):

Let $\phi^+(x)$ ($\phi^-(x)$) denote the piece of $\phi(x)$ which depends on the creation (annihilation) operators only, $$\phi(x) ~=~\phi^+(x)+\phi^-(x).\tag{5.262}$$

The corrected eq. (5.284) is derived as follows:

$$ :e^A::e^B:~=~e^{A^+}e^{A^-}e^{B^+}e^{B^-}~=~e^{A^+}e^{[A^-,B^+]}e^{B^+}e^{A^-}e^{B^-}$$ $$~=~e^{[A^-,B^+]}e^{A^++B^+}e^{A^-+B^-}~=~e^{[A^-,B^+]}:e^{A+B}:\tag{5.284'}$$


  1. E. Fradkin, Field Theories of Condensed Matter Physics, 2nd ed. (2013).


$^1$ Independently, there is a wrong sign in the truncated BCH formula (5.269).

$^2$ Alternatively, eq. (5.284) is correct in its printed form if we use the opposite notation for creation & annihilation operators.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.